Field experiments with firms - Oriana Bandiera; Iwan Barankay; Imran Rasul (Institute for the Study of Labor (IZA), 2011)
We discuss how the use of field experiments sheds light on long standing research questions relating to firm behavior. We present insights from two classes of experiments: within and across firms, and draw common lessons from both sets. Field experiments within firms generally aim to shed light on the nature of agency problems. Along these lines, we discuss how field experiments have provided new insights on shirking behavior, and the provision of monetary and non-monetary incentives. Field experiments across firms generally aim to uncover firms' binding constraints by exogenously varying the availability of key inputs such as labor, physical capital, and managerial capital. We conclude by discussing some of the practical issues researchers face when designing experiments and by highlighting areas for further research.
urn:nbn:de:101:1-201106013376
Keywords: C9; M5; 330; field experiments; firms; organizations